SOCIAL DYNAMICS OF TIMOR TIMUR SOCIETY DURING THE UNIFICATION ERA WITH INDONESIA IN ORANG-ORANG OETIMU’S BY FELIX K. NESI: DINAMIKA SOSIAL MASYARAKAT TIMOR TIMUR ERA UNIFIKASI DENGAN INDONESIA DALAM NOVEL ORANG-ORANG OETIMU KARYA FELIX K. NESI - Devi Hari Fitriya Ningsih; Eggy Fajar Andalas (Jurnal Kata : Penelitian tentang Ilmu Bahasa dan Sastra, 2021)
The main impact of the unification era of East Timor with Indonesia is the social dynamics. The purpose of this study is to find out the social dynamics of the East Timor people that occurred in the era of unification with Indonesia in the Orang Orang Oetimu novel. This study uses a postcolonial approach. The research method is qualitative. The data source of this research is the Orang-Orang Oetimu by Felix K. Nesi. The data collection technique was done by contrapuntal technique, the reading strategy suggested by Said. The technique of analyzing data are presentation of data, grouping data and drawing conclusions. The results showed that the social dynamics that occurred in the era of Indonesian occupation in East Timor were the amount of corruption committed by state officials resulting in social inequality, the hypocrisy of religious leaders in East Timor, and the desire of East Timor to be independent.